2023
DOI: 10.3390/jcm12041646
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Pan-Cancer Analysis of MEIS1 in Human Tumors as Prognostic Biomarker and Immunotherapy Target

Abstract: Background: We intended to explore the potential immunological functions and prognostic value of Myeloid Ecotropic Viral Integration Site 1 (MEIS1) across 33 cancer types. Methods: The data were acquired from The Cancer Genome Atlas (TCGA), Genotype-Tissue Expression (GTEx) and Gene expression omnibus (GEO) datasets. Bioinformatics was used to excavate the potential mechanisms of MEIS1 across different cancers. Results: MEIS1 was downregulated in most tumors, and it was linked to the immune infiltration level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…FGSEA analysis further proves that MEIS1 co-expressed with cell cycle, DNA repair, and DNA metabolic process genes. A study revealed a high correlation between MEIS1 expression and the majority of immune cells in various cancers (Li et al 2023 ). For example, the FTO/RP5-991G20.1/hsa-miR-1976/MEIS1 regulatory axis is necessary for regulating the infiltration of immune cells and prognosis in ovarian cancer patients (Chen et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…FGSEA analysis further proves that MEIS1 co-expressed with cell cycle, DNA repair, and DNA metabolic process genes. A study revealed a high correlation between MEIS1 expression and the majority of immune cells in various cancers (Li et al 2023 ). For example, the FTO/RP5-991G20.1/hsa-miR-1976/MEIS1 regulatory axis is necessary for regulating the infiltration of immune cells and prognosis in ovarian cancer patients (Chen et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer overlook lung cancer as the most frequently diagnosed cancer worldwide in 2020, accounting for nearly 12% of new cases [ 1 ]. Breast cancer cells show metabolic abnormalities and mitochondrial oxidative stress, and various tumor marker proteins are increased [ 2 , 3 , 4 ]. A combination of preoperative chemotherapy and surgery is the current treatment strategy for breast cancer patients.…”
Section: Introductionmentioning
confidence: 99%